The Influence of Education Level, Population, and Wages on Employment Absorption in Regencies/Cities of Bali Province - I Nyoman Agus Wiranata; Ni Made Tisnawati (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Labor absorption is an important issue in the development of a region. Labor can be used as a benchmark for success in the development of a region. This study aims to analyze the effect of education level, population, and wages on labor absorption in the districts/cities of Bali Province using secondary data from 2017-2023. Data collection uses the observation method and is analyzed using panel data regression with the help ofsoftwareE-Views 12. The results of the study indicate that the level of education, population, and wages simultaneously have a significant effect on labor absorption. Partially, the level of education has a negative but not significant effect on labor absorption, the population has a significant positive effect on labor absorption, and wages have a significant negative effect on labor absorption. The district/city governments in Bali Province should pay more attention to the education sector, by increasing the quality of education through the development of infrastructure and supporting facilities, it is hoped that this will be able to increase labor absorption which will ultimately encourage economic development. In addition, the district/city governments of Bali Province must be more sensitive to the potential of their respective regions so that existing funds can be utilized properly to improve people's standard of living through income equality